HUBUNGAN PERSEPSI KARIR, DISIPLIN KERJA, MOTIVASI KERJA DENGAN KINERJA GURU - Eka Fitri Yanti; Sudjarwo Sudjarwo; Sumadi Sumadi (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to determine the correlation between career perceptions, discipline, work motivation of social science and citizenship teachers towards teachers performance. The method used in this research was analytical quantitative with correlation associative. The result of this research stated that: (1) there is a significant correlation between career perception towards teachers performance with partial correlation coefficient of 0.282%; (2) there is a significant correlation between work discipline towards teachers performance with partial correlation coefficient of 0.381%; (3) there is a significant correlation between work motivation towards teachers performance with partial correlation coefficient of 0.538%; (4) there is a significant correlation between perceptions of career, work discipline, and work motivation towards teachers performance with multiple correlation coefficient of 0.545% with a positive correlation. Thus, the better the perception of careers, work discipline, and work motivation towards teachers performance, then the better it will be.Penelitian ini bertujuan untuk mengetahui hubungan persepsi karir terhadap kinerja guru, motivasi kerja terhadap kinerja guru IPS dan PKn. Metode yang digunakan adalah kuantitatif menggunakan cara analitik, yaitu dengan assosiatif korelasi. Hasil penelitian menyatakan: (1) ada hubungan yang signifikan persepsi karir terhadap kinerja guru dengan koefisien korelasi parsial sebesar 0,282 %; (2) ada hubungan yang signifikan disiplin kerja terhadap kinerja guru dengan koefisien korelasi parsial sebesar 0,381 %; (3) ada hubungan yang signifikan motivasi kerja terhadap kinerja guru dengan koefisien korelasi parsial sebesar 0,538 %; (4) ada hubungan yang signifikan persepsi karir, disiplin kerja, dan motivasi kerja terhadap kinerja guru dengan koefisien korelasi ganda sebesar 0,545 % pada pengaruhpositif. Dengan demikian semakin baik persepsi karir, disiplin kerja, dan motivasi kerja maka akan semakin baik pula kinerja guru.Kata kunci: disiplin kerja, kinerja guru, motivasi kerja, persepsi karir